CLONING AND SEQUENCING OF A MITOCHONDRIAL AUTOANTIGEN WITH IMMUNOGLOBULIN G FROM PATIENTS WITH MULTIPLE SCLEROSIS (Journal of Sciences, Islamic Republic of Iran)
Multiple Sclerosis (MS) is a chronic neurological disease of the central nervous system (CNS), characterised by a cellular immune response in early stages and demyelination of the CNS later. Although the cause of MS is unknown, there is much evidence that points to MS as an autoimmune disease. To test the hypotheses that an Autoantigen is involved in MS, we screened a ?gt11 human foetal spinal cord cDNA library using IgG from patients with MS. From screening 2×106 recombinant phage, 6 positive clones were identified. Properties expressed by these lambda phage on the bacterial lysate plate appeared to react specially with pooled MS IgG but not with pooled IgG purified from normal human sera. The positive clones were amplified by the polymerase chain reaction (PCR) and sequenced. After searching in GenBank analysis of the sequences showed a high percent similarity between three clones called M64, M63 and M62 (0.6, 0.9 and 1.8 Kb length, respectively) and the mitochondrial gene encoding the human NADH:ubiquinone reductase (complex I). This is the first time a mitochondrially encoded protein has been shown to be an autoantigen. This discovery adds to the growing list of intracellular enzymes which are considered as involved autoantigens in autoimmune diseases.